Sutura: social life, protection and intimacies - Falcão, Ricardo (VII Congresso da Associação Portuguesa de Antropologia, 2019)
Sociocultural values are often said to play a role on the interpretation of the meaning of cultural practices and social norms. In international forums, conferences, workshops,  development campaigns, or in political discourse, the idea that cultural references should be taken into account is often present and motivates frequent debates on legitimacy (and its sources). But despite that, the full implications of cultural diversity are seldomly explored and are in fact overlooked, quickly substituted by more abstract, transcultural generalizations. In this paper, by discussing the sociocultural value of «sutura» and its importance to the context of communication and meaning in senegalese-wolof cultural landscape I will stress the need to question conceptual assumptions related with communicative frameworks where human rights language is promoted. Sutura, often plays an important role in what people choose to say or keep to themselves, working as a form of secrecy. It is also an ethical stance, a form of social protection (with both positive and negative consequences), but also a value exchanged in social interaction, closely knitted with gender roles and intimacy. Despite its social relevance most of the references to it are slim and quick understatements of its true importance as a cultural marker.